2021
DOI: 10.3390/ijms22041680
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Antidiabetic Medications and Cancer Risk in Type 2 Diabetes: Focus on SGLT-2 Inhibitors

Abstract: In the last decade, cancer became the leading cause of death in the population under 65 in the European Union. Diabetes is also considered as a factor increasing risk of cancer incidence and mortality. Type 2 diabetes is frequently associated with being overweight and obese, which also plays a role in malignancy. Among biological mechanisms linking diabetes and obesity with cancer hyperglycemia, hyperinsulinemia, insulin resistance, increased levels of growth factors, steroid and peptide hormones, oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 135 publications
(256 reference statements)
0
24
0
1
Order By: Relevance
“…The overexpression of SGLT-2 was observed in pancreatic cancer cells ( Scafoglio et al, 2015 ). By blocking SGLT-2, a reduced PDA risk was found in SGLT-2 inhibitor users, and a decreased cancer proliferation in preclinical pancreatic cancer models when treated with SGLT-2 inhibitor ( Dicembrini et al, 2019 ; Dąbrowski, 2021 ).…”
Section: Clinical Advances Of Targeting Insulin and Insulin Signal Pa...mentioning
confidence: 99%
“…The overexpression of SGLT-2 was observed in pancreatic cancer cells ( Scafoglio et al, 2015 ). By blocking SGLT-2, a reduced PDA risk was found in SGLT-2 inhibitor users, and a decreased cancer proliferation in preclinical pancreatic cancer models when treated with SGLT-2 inhibitor ( Dicembrini et al, 2019 ; Dąbrowski, 2021 ).…”
Section: Clinical Advances Of Targeting Insulin and Insulin Signal Pa...mentioning
confidence: 99%
“…Studies have found that patients who use metformin have a lower risk of cancer and lower cancer-related mortality [ 10 , 11 ]. Some experimental studies have found that metformin can inhibit the proliferation of prostate cancer cells [ 12 ], breast cancer cells [ 13 ], pancreatic cancer cells [ 14 ], and melanoma cells [ 15 ] in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-diabetic drugs can affect cancer risk both directly and indirectly by affecting cancer cell metabolism and risk factors. Metformin has beneficial effects in many site-specific cancers, lowering the incidence of liver, gastric, colorectal, endometrial and breast cancers, with reducing the mortality and improving the survival from lung, colorectal, prostate, endometrial, pancreatic and breast cancers[ 86 ]. Metformin reduces the risk of neoplastic and pre-neoplastic cell proliferation by decreasing production of hepatic glucose and increasing glucose uptake peripherally, primarily by the muscle cells.…”
Section: Antidiabetic Medication and Risk Of Skin Cancersmentioning
confidence: 99%